Mean Platelet Volume in Cirrhotic Patients with Ascitic Fluid Infection - Muhammad Nadeem, Muhammad Farooq Khan, Iftikhar Ali Kakar, Shair Zaman Khan, Haris Khan, Mehreen Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Ascites is the most prevalent clinical symptom of cirrhosis and hepatic decompensation. Patients with cirrhosis are often more likely to get bacterial infections, particularly ascitic fluid infection, which affects 15-20% of people with ascites and cirrhosis Objective: To determine mean platelet volume in cirrhotic patients with ascitic fluid infection. Material and methods: The current study was descriptive and cross-sectional carried out at the department of Medicine Lady Reading Hospital Peshawar for duration of six months from January 2022 to July 2022. From all the patients, a 10cc blood and 20cc ascitic fluid was obtained under aseptic conditions and was sent immediately to hospital diagnostic laboratory for measurement of MPV from blood and Poly-morphonuclear cells in the ascitic fluid. Data analysis was done by employing SPSS version 17. Results: In the current study, male patients were 129(62%) while female patients were 79(38%). The mean age (±SD) in the current study was 42 (±1.88) years. Based on platelet volume, 46(22%) patients had platelet volume range from 7.6- 8.5 fl, 100(48%) patients had platelet volume range 8.6- 9.5 fl, 62(30%) patients had platelet volume range 9.6- 11.5 fl. Mean platelet volume was 9.12 fl with SD ± 1.21. Conclusion: Our study concludes that MPV levels increase significantly in cirhhotic patients with ascitic fluid infection therefore MPV measurement might be thought of as an accurate diagnostic tool for predicting ascitic fluid infection. Keywords: Mean platelet volume; cirrhotic patients; ascitic fluid infection